1997
DOI: 10.1523/jneurosci.17-13-05183.1997
|View full text |Cite
|
Sign up to set email alerts
|

Memory Representation within the Parahippocampal Region

Abstract: The activity of 378 single neurons was recorded from areas of the parahippocampal region (PHR), including the perirhinal and lateral entorhinal cortex, as well as the subiculum, in rats performing an odor-guided delayed nonmatching-to-sample task. Nearly every neuron fired in association with some trial event, and every identifiable trial event or behavior was encoded by neuronal activity in the PHR. The greatest proportion of cells was active during odor sampling, and for many cells, activity during this peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
297
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(331 citation statements)
references
References 65 publications
(74 reference statements)
28
297
0
3
Order By: Relevance
“…This discrepancy probably stems from a combination of MR technical (Kaza et al 2011;Ojemann 1997Ojemann , 2010 issues combined with local anatomic-physiologic characteristics of odor processing in the entorhinal cortex. In rats entorhinal neurons display odor selectivity (Young et al 1997), and thus both inter-and intraindividual activity to the identified odors may differ, thus contributing to a limited area of activation in the third level group analysis, although activity for each individual was high, as shown in the functional and anatomic entorhinal ROI analyses. These findings provide direct evidence for the proposed connection between entorhinal pathol- The model for spontaneous identified vs. nonidentified odors was event-related.…”
Section: Discussionmentioning
confidence: 98%
“…This discrepancy probably stems from a combination of MR technical (Kaza et al 2011;Ojemann 1997Ojemann , 2010 issues combined with local anatomic-physiologic characteristics of odor processing in the entorhinal cortex. In rats entorhinal neurons display odor selectivity (Young et al 1997), and thus both inter-and intraindividual activity to the identified odors may differ, thus contributing to a limited area of activation in the third level group analysis, although activity for each individual was high, as shown in the functional and anatomic entorhinal ROI analyses. These findings provide direct evidence for the proposed connection between entorhinal pathol- The model for spontaneous identified vs. nonidentified odors was event-related.…”
Section: Discussionmentioning
confidence: 98%
“…Although we did not establish a contribution of hippocampal CCK, the Fos analysis suggests that CA1 neurons contribute to the expression of associative morphine tolerance. The hippocampus seems to serve as a locus for memory consolidation and to perform the match-mismatch discriminations necessary for memory recognition 46 . Moreover, there are direct, reciprocal connections between the hippocampus and L/BL amygdala 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Rats with perirhinal-entorhinal lesions were found to be impaired in an olfactory recognition memory tasks (Kaut and Bunsey, 2001;Kaut et al, 2003). Electrophysiological recordings during delayed non-matching tasks also show a role for the perirhinal cortex (Young et al, 1997) and prefrontal cortex (Ramus and Eichenbaum, 2000) in olfactory discrimination. Bearing in mind the anatomical connections between the perirhinal cortex and olfactory regions (see Section 3.2) and that many object recognition studies in rats rely on nose contact as a measure of exploration, it is surprising that more attention has not been focussed on the role of the perirhinal cortex in olfactory recognition memory.…”
Section: Object Recognition Memorymentioning
confidence: 91%
“…3a; Swanson and Cowan, 1977;Wyss, 1981;Kosel et al, 1982Kosel et al, , 1983Deacon et al, 1983;Kö hler, 1988;Van Groen and Wyss, 1990;Insausti et al, 1997;Burwell and Amaral, 1998a,b;Shi and Cassell, 1999;Kloosterman et al, 2003b). Based on anatomical (Witter et al, 2000b;Witter, 2002), electrophysiological (Young et al, 1997;Ivanco and Racine, 2000;Naber et al, 1997Naber et al, , 1999Naber et al, , 2001a and functional evidence (Bussey et al, 2000;Wan et al, 2001;Burwell et al, 2004a,b;Jenkins et al, 2004;Amin et al, 2006;Albasser et al, 2010;Romero-Granados et al, 2010), the hippocampal-parahippocampal region of the brain has been implicated in several aspects of learning and memory. The role of the perirhinal cortex in this hippocampal-parahippocampal network has been traditionally seen as a gateway for sensory information into the hippocampus via the entorhinal cortex (Witter et al, 2000a,b) but, as discussed below, the current evidence does not fully support this model but points to a more complex relationship between the hippocampal-parahippocampal regions.…”
Section: Hippocampal and Parahippocampal Projectionsmentioning
confidence: 99%